The Solvatochromism of Phenolate Betaines: Comparing Different Cavities of a Polarized Continuum Model - Caroli-Rezende, M; Dominguez-Caru, M (Springer Verlag, 2015)
Two variations of the polarized continuum model employing default (“PCM model”) and SMD radii (“SMD model”) were compared for the reproduction of the solvatochromic behavior of Reichardt’s betaine dye, and of eight other phenolate betaines that exhibit a negative, positive or an inverted solvatochromic behavior. Molecules were optimized at the CAM B3LYP/6-31+G(d,p) level of theory, and transition energies were calculated with the TD-DFT method. The PCM model failed to reproduce the negative and the inverted solvachromism of these dyes in protic solvents. The SMD model, though not entirely accounting for hydrogen-bond effects in small, polar hydroxylic solvents, should be recommended as a better alternative for the theoretical simulation of the solvatochromism of phenolate betaines in medium to highly polar solvents. [Figure not available: see fulltext.] © 2015, Springer-Verlag Berlin Heidelberg.
Keywords: Phenolate betaines; Polarized continuum model (PCM); Positive, negative and reverse solvatochromism; Universal solvation model (SMD)